The industrially important genus Kaempferia: An ethnopharmacological review - Singh, Arpit; Singh, Nitesh; Singh, Sanchita; Srivastava, Ravi Prakash; Singh, Lav; Verma, Praveen C.; Devkota, Hari P.; Rahman, Laiq ur; Kumar Rajak, Bikash; Singh, Amrita; Saxena, Gauri (Frontiers in Pharmacology, 2023)
Kaempferia, a genus of the family Zingiberaceae, is widely distributed with more than 50 species which are mostly found throughout Southeast Asia. These plants have important ethnobotanical significance as many species are used in Ayurvedic and other traditional medicine preparations. This genus has received a lot of scholarly attention recently as a result of the numerous health advantages it possesses. In this review, we have compiled the scientific information regarding the relevance, distribution, industrial applications, phytochemistry, ethnopharmacology, tissue culture and conservation initiative of the Kaempferia genus along with the commercial realities and limitations of the research as well as missing industrial linkages followed by an exploration of some of the likely future promising clinical potential. The current review provides a richer and deeper understanding of Kaempferia, which can be applied in areas like phytopharmacology, molecular research, and industrial biology. The knowledge from this study can be further implemented for the establishment of new conservation strategies.